2016
DOI: 10.1080/09553002.2016.1206238
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of α-particle-induced chromosomal aberrations by chemically-induced PCC. Elaboration of dose-effect curves

Abstract: In a similar way to high-dose exposures to low-LET radiations, cells show difficulties reaching mitosis after high-LET radiation exposure. For this reason, techniques have been proposed that are able to analyze chromosome aberrations in interphase by prematurely condensing the chromosomes (PCC-techniques). Few dose-effect curves for high-LET radiation types have been reported, and none for α-particles. The aim of this study was to evaluate, by chemically-induced PCC, the chromosome aberrations induced by sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
2
4
0
1
Order By: Relevance
“…The number of DC and MN observed in the PBLs has been plotted against the AD to blood. A linear correlation (increase) has been found between AD to blood and DC number as reported for other radionuclides [ 11 , 18 , 31 ].…”
Section: Discussionsupporting
confidence: 64%
“…The number of DC and MN observed in the PBLs has been plotted against the AD to blood. A linear correlation (increase) has been found between AD to blood and DC number as reported for other radionuclides [ 11 , 18 , 31 ].…”
Section: Discussionsupporting
confidence: 64%
“…The same received dose may result in dissimilar cytotoxic and genotoxic effects. Observed differences in response to various types of radiation may result from many patient factors [33]. The genetic component is significant for individual radiosensitivity; however, environmental factors, lifestyle, diet, physical activity, and hormonal status also influence the observed effects [8,34].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, over dispersion of dicentrics was observed beyond 4.6 mGy. Puig et al [12] showed an initial increase in dicentric distribution with over dispersion for 0.05 Gy, 0.1 Gy and there was decline till 2.5 Gy. Many other authors had similar observation in the over dispersion [13,16].…”
Section: Discussionmentioning
confidence: 95%
“…There are many reports on dose response curve for low LET radiation [8][9][10] and for high-LET radiation using PCC assay [8,11] and none of them for alpha particles. However, there is one recent report about the dose response for α-particles with the maximum dose of 2.5 Gy [12]. But till date no report exists for dose response curve of radon using PCC technique.…”
Section: Discussionmentioning
confidence: 99%